Importance of spin current generation and detection by spin injection and the spin Hall effect for lateral spin valve performance. (25th October 2018) - Pfeiffer, A; Reeve, R M; Kläui, M
Abstract: Lateral spin valves are attractive device geometries where functional spin currents can be generated and detected by various mechanisms, such as spin injection and the direct and the inverse spin Hall effect. To understand the mechanisms behind these effects better, as well as their potential for application in devices, we combine multiple mechanisms in multi-terminal Pt–Py–Cu lateral spin valves: we generate pure spin currents in the copper spin conduit both via the spin Hall effect in platinum and electric spin injection from permalloy and detect signals both via conventional non-local detection and via the inverse spin Hall effect in the same device at variable temperatures. Differences are observed, which we explain by the different spin injection and detection mechanisms, revealing their importance for the temperature dependence, which is not just governed by the spin transport in the conduit as previously claimed. By determining a different sensitivity of the observed effects on the interfaces, we highlight the importance of the exact current path for the device operation.